A comparison on the detection accuracy of ante mortem computed tomography vs. autopsy for the diagnosis of pelvic ring injury in legal medicine. Issue 3 (29th January 2021) - Höch, Andreas; Özkurtul, Orkun; Hammer, Niels; Heinemann, Axel; Tse, Rexson; Zwirner, Johann; Henkelmann, Jeanette; Fakler, Johannes; Ondruschka, Benjamin
Abstract: A detailed knowledge on the exact morphology of pelvic injuries provided crucial information in understanding the mechanisms of injury and has influence on the natural course and subsequent mortality. However, forensic medical literature investigating pelvic fractures in detail is scarce to date. This case series aims to compare the accuracy in detecting pelvic injuries using autopsy and ante mortem computed tomography (CT). Nineteen deceased patients with CT scans of pelvic fractures were included retrospectively. Pelvic injuries were independently assessed by a board‐certified radiologist (R) and a board‐certified trauma surgeon (T), both using the ante mortem CT scans, and by a board‐certified forensic pathologist using autopsy (A) results without knowledge of the CT scan findings. No patient had died causatively from a pelvic fracture. Most injuries of the pelvis were present in the pubic rami (16/18) and sacral bone (13/18), followed by the sacroiliac joint (9/18) and iliac bone fractures (8/18). Ilium fractures (A:100%;R:67%;T:67%) and injuries of the sacroiliac joint (A:83%;R:50%;T:42%) were best detected via autopsy. The diagnosis of sacral fractures (A:19%;R:94%;T:88%) and fractures of the pubic rami (A:67%;R:96%;T:96%) were most often missed in autopsy. The results show deficits in the assessment of the pelvic injury for both CT and autopsy. Autopsy was superior in detecting injuries of the sacroiliac joint, but inferior in detecting sacral and pubic bone fractures. For an encompassing evaluation of ligamento‐skeletal pelvic injuries, the complementary use of both CT and autopsy is recommended.